A Fourteenth-Century Scholastic Dispute on Astrological Interrogations - Nothaft, Carl (My University, 2021)
This article examines and edits an anonymous text from the late 1330s (Quesitum fuit utrum per interrogationes …), which was written to refute the arguments presented in a lost quaestio disputata by an unknown Parisian philosopher. At the heart of this scholastic dispute was the question whether the astrological branch known as interrogations was an effective and legitimate means of predicting the future. The philosopher’s negative answers to this question as well as the rebuttals preserved in our anonymous text offer valuable new insights into the debate over astrology that raged at the University of Paris during the fourteenth century. Besides arguing at length for the internal coherence and philosophical soundness of interrogations, the text contains a bold defence against the Augustinian view that astrologers consort with demons. This defence was later rebutted as part of an anti-astrological polemic by the astronomer Heinrich Selder, who is known to have studied in Paris during the 1370s.
PUBLISHED
Keywords: Astrology; Astronomy; Philosophy; Manuscript, Book and Print Cultures; History